Multi-objective optimization of full depth reclamation with Portland cement using NSGA-II for sustainable pavement rehabilitation - Xia, Qing; Zhang, Haiwei; Miao, Wang; Guo, Xiaogang; Zhang, Qingqing (Frontiers in Built Environment, 2025)
Full-depth reclamation with Portland cement (FDR-PC) is a promising technology in modern pavement engineering due to its capability of achieving deep-level treatment of pavement base layer distresses. This study aimed to optimize the material performance of FDR-PC materials while considering their environmental impact, developing a multi-objective optimization model to comprehensively evaluate and optimize these aspects. Laboratory tests were first conducted to investigate the effects of reclaimed asphalt pavement (RAP) content and cement content on 7-day unconfined compressive strength (UCS), indirect tensile strength (ITS), and relative compressive strength (RCS) after freeze-thaw cycles. A comprehensive performance evaluation function was established based on these key indicators. Subsequently, carbon emission and energy consumption models for FDR-PC were developed using life cycle assessment (LCA), which together formed an environmental impact function. The non-dominated sorting genetic algorithm II (NSGA-II) was employed to perform multi-objective optimization of the FDR-PC mix design and obtain the Pareto front. The technique for order of preference by similarity to ideal solution (TOPSIS) was then used to identify optimal parameter combinations under various objective weighting scenarios. Results revealed a significant negative correlation between material performance and environmental impact. The parameter combinations corresponding to the non-dominated solutions were mainly concentrated in cement content ranging from 4.8% to 6.0% and RAP content from 20% to 34%. Parameter combinations corresponding to high material performance were found in regions with RAP content below 20%, which also corresponded to high environmental impact. According to the TOPSIS analysis, the optimal mix under a performance-priority strategy consists of 6.0% cement and 5% RAP; the environmentally preferred mix recommends 4.6% cement and 32% RAP; and a balanced compromise suggests 5.2% cement and 27% RAP.